Omnichannel Marketing Strategy and Product Quality Perception in Building Non-Pso Fuel Customer Loyalty with Customer Satisfaction as a Mediator - Agus Santosa; Metta Padmalia; Endi Sarwoko (Eduvest - Journal of Universal Studies, 2026)
The Indonesian fuel industry faces significant challenges in promoting non-PSO fuel adoption, particularly following the February 2025 product quality controversy that resulted in an 11% decline in Pertamax sales. Despite non-PSO fuels generating substantially higher profit margins (up to 11% vs. 0.2% for subsidized fuel), consumer preference remains heavily skewed toward subsidized options due to price sensitivity and declining brand trust. This study aims to analyze the mediating role of customer satisfaction in the relationship between omnichannel marketing strategy and product quality perception on non-PSO fuel customer loyalty. The research employs a quantitative approach with purposive sampling targeting 256 respondents who have used non-PSO fuel within the last three months and are familiar with MyPertamina application features. Data collection utilizes validated instruments adapted to the Indonesian energy context, measured through 5-point Likert scales. Analysis employs Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine direct effects, mediation relationships, and model fitness. This research expands Customer Relationship Management theory and omnichannel marketing literature within the underexplored energy sector. The study finds that, in the Indonesian energy context, product quality perception is the strongest driver of customer satisfaction for non-PSO fuels (β=0.706), surpassing the influence of omnichannel marketing strategy (β=0.235). Customer satisfaction fully mediates the relationship between omnichannel marketing strategy and loyalty and partially mediates the effect of product quality perception on loyalty, reinforcing the dominant role of product quality even amid digital transformation.